Restored and Enhanced Memory T Cell Immunity in Rheumatoid Arthritis After TNFα Blocker Treatment - Khanniche, Asma; Zhou, Ling; Jiang, Bin; Song, Jing; Jin, Yanhua; Yin, Jian; Wang, Shujun; Ji, Ping; Shen, Hao; Wang, Ying; Xu, Huji (Frontiers in Immunology, 2019)
TNFα inhibitors have shaped the landscape of rheumatoid arthritis (RA) therapy with high clinical efficiency. However, their impact on T cell recall responses is not well elucidated. We aimed to analyze the immune profiles of memory T cells in RA patients undergoing TNFα inhibitor Golimumab (GM) treatment. Frequencies of peripheral T cell subsets and cytokine expression profiles in memory T cells (TM) upon PMA/Ionomycine stimulation were determined by flow cytometry. Antigen-specific CD8 T cell immunity was analyzed through stimulating PBMCs with CMV-EBV-Flu (CEF) viral peptide pool and subsequent intracellular IFNγ staining. Both peripheral CD8 and CD4 T cells from GM treated patients had a shift pattern characterized by an enlarged effector TM and a reduced central TM cell population when compared to GM untreated group. An increase in the frequencies of TNFα+, IL-2+ and IL-17+ CD8 TM cells was observed whereas only TNFα+CD4 TM cells increased in GM treated patients. Moreover, GM treated patients contained more peripheral IFNγ-producing CD8 T cells specific to CEF viral peptides. Together, these results show a distinct T cell subset pattern and enhanced memory T cell immunity upon GM treatment, suggesting an immunoregulatory effect of TNF inhibitor Golimumab on peripheral memory T cell responses.